Dialectical conditions: Leadership structures as productive action generators - Albert Martin (Management Revue, 2006)
This article introduces a model of productive leadership structures. It is based on the idea that structures should stimulate dialectical processes which activate functional and simultaneously restrict dysfunctional behavioural tendencies of the management team. The structural dialectics are part of a more comprehensive concept called 'tensegrity', which, besides the dialectic part, embraces the socio-political conditions in the leadership system which enable dialectic structures to unfold their positive energy. In the second part of the article I present the results of an empirical study conceived to test some basic hypotheses of the theoretical approach.
Keywords: 650; decision-making; leadership structures; top management teams; contradictions; dialectics; tensegrity; structuration; Führungskräfte; Entscheidung; Organisationsstruktur; Führungsstil; Deutschland